Reassessing the emergency department burden of influenza: A comprehensive real-world analysis using administrative data - Dariush Khezrimotlagh; Sara Imanpour; Erol Akbas (PLoS ONE, 2026)
Emergency departments (EDs) are burdened by high patient volumes during influenza seasons, yet the clinical and operational profile of influenza visits remains underexamined in large-scale data. This study analyzes a stratified sample of more than 5.5 million patient records from the New York State Emergency Department Database (SEDD) in 2019 to assess the comorbidity burden, outcomes, resource utilization, and readmission patterns of influenza visits compared to all other emergency department encounters. The objective is to determine whether influenza visits reflect higher severity and health system strain or lower-acuity cases suitable for alternative care settings. Influenza visits show lower comorbidity burden, no observed mortality, lower total charges, and shorter lengths of stay. Patients with influenza have fewer overall readmissions, longer average time before return, and substantially lower thirty-day readmission rates than patients with non-influenza diagnoses. These findings indicate that influenza ED visits are lower in complexity and resource burden. By linking comorbidity adjusted severity with real world outcomes, this study provides empirical evidence to guide seasonal care planning and resource allocation.